A MODELING OF A DAMPING OF THE SLOW MAGNETOACOUSTIC WAVES IN A HIGHTEMPERATURE PLASMA - S. B. Derteev; G. A. Mankaeva; M. E. Sapraliev; A. K. Baltykov; D. B. Bembitov (Современная наука и инновации, 2023)
Linear analysis still uses a simplified local representation of the plasma radiative loss function as a degree of temperature [1], which, in our opinion, leads to large errors in the results. The behavior of the magnetoacoustic waves strongly depends on the parameters of the plasma; therefore, a more precise analytical expression for the radiatiave loss function is needed. We use new data on the radiative loss function [2]. We build local analytical expressions using cubic splines and study wave attenuation in a wide range of plasma and magnetic field parameters.